Population growth of green mussel, perna viridis linnaeus from southern part of the Malacca straits - Kassim, Zaleha; Omar, Mohd Luthfi; Jasmani, Safiah (Malaysian Society of Applied Biology, 2017)
Perna viridis Linnaeus, or locally known as green mussel or green-lipped mussel, has been cultivated in Malaysia since the early 1970s. Despite the advanced research and development for green mussels in Malaysia, the mass production had been limited to some areas such as Teluk Danga Johor and Kesang area, Sebatu in Melaka which could be due to the environmental factors. This study aimed to evaluate the growth and exploitation level of green mussel in one of the most popular place for green mussel production in Malaysia, the Kesang coastal area in the Straits of Malacca. It will become significant model for the growth and could be used as the benchmark for status of this natural resource. Samples of P. viridis were collected from those attached to rope collectors firstly deployed during the early months of the study period. 400 nylon rope collectors with 2m long and attached with weighted brick on each bottom were set up. Spats of P. viridis used the rope collector as their substrates to grow. Each collector was placed on the bamboo with 1 meter interval and three rope collectors were taken randomly and preserved with 10% formalin. Frequency data were obtained from the measurement of 168 samples each month. The growth for the first three months was seen between September and December 2007 with high percentage of spat in the size range of 10-15mm and 25-35mm respectively. The frequency of the size ranged between 60-80%. This indicated the fast growing month for the spats. The growth rate slowed down as they increase their age. Based on the reconstructed curve, the growth performance index (ϕ’) was 3.983, as quantified by the ELEFAN-1of FiSAT software. The growth constant K= 0.66 year-1, which is a curvature parameter determined how fast is the mussel approaches its L∝.The growth constant from this study showed lower value with 0.66-year-1 compared to other similar studies in Malaysia. Further study is required to determine the growth response of P. viridis towards fluctuation of sea water quality in the sea farming area. Control on harvesting wild stock in the area is suggested as to sustain the source of wild seed in future.